Spectral-Domain Optical Coherence Tomographic Assessment of Schlemm's Canal in Chinese Subjects with Primary Open-angle Glaucoma - Hong, Jiaxu; Xu, Jianjiang; Wei, Anji; Wen, Wen; Chen, Junyi; Yu, Xibao; Sun, Xinghuai (Ophthalmology (Rochester, Minn.), 2013)
To evaluate in vivo features of Schlemm's canal (SC) in patients with primary open-angle glaucoma (POAG) with spectral-domain optical coherence tomography (SD-OCT) and to investigate the relationship of SC size with intraocular pressure (IOP) and glaucoma severity. Prospective, comparative study. Fifty Chinese patients with newly diagnosed POAG who had not undergone surgery and 50 normal Chinese subjects from a population-based, cross-sectional study in Shanghai. All participants underwent SD-OCT. The diameter and area of SC were examined in the temporal and nasal sections and measured with customized software. Patient demographics, repeatability and reproducibility assessed with the coefficient of variation (CV) and the intraclass correlation coefficient (ICC), SC parameters and their correlation with IOP, and the mean deviation (MD) of the visual field were analyzed. The percentage of sections in which SC was observable was similar between eyes with POAG and normal eyes, and ranged from 78% to 86%. For intraobserver repeatability, the CV and ICC values were 7.9% and 0.97 for diameter, and 13.8% and 0.83 for area, respectively. For interobserver repeatability, the CV and ICC values were 13.6% and 0.89 for diameter, and 13.4% and 0.80 for area, respectively. Significant differences between the 2 groups were found for the average SC area (11332±2015 μm2 vs. 13991±1357 μm2; P<0.001), but not for the SC diameter (40.2±7.1 μm vs. 45.2±4.0 μm; P = 0.195). In addition, the mean IOP values correlated well only with the SC area (ρ = −0.674, P<0.001), not with the SC diameter (ρ = −0.103, P = 248). No significant correlations were found between the MD values and the SC parameters. Eyes with POAG have a decreased SC area compared with normal eyes. A correlation between the SC area and the IOP also was observed. However, the degree of glaucoma damage was not consistently associated with the SC area. Spectral-domain OCT could be used for investigating SC changes in patients with glaucoma. The author(s) have no proprietary or commercial interest in any materials discussed in this article.